A Paradise for Rare Species: Tanaidacean Fauna of the West African Continental Margin - Jóźwiak, Piotr; Pabis, Krzysztof; Sobczyk, Robert; Serigstad, Bjorn (Frontiers in Marine Science, 2022)
The benthic ecology of the Gulf of Guinea is critically understudied, and knowledge about the composition and biodiversity of the tanaidacean communities remains lacking. Our analysis of tanaidacean collection from 270 quantitative samples collected using 0.1 m2 van Veen grab along the Ghanaian coast (nine transects, six stations at each transect, 25–1,000 m depth range) reveals a high species richness and very low abundance. The mean density of Tanaidacea across all the samples equals only 0.03 ± 0.55 ind./0.1 m2. A total of 87 tanaidacean species were recorded, of which only three were known for science (3.4%), emphasizing the need for intensified taxonomic effort in this region. Circa 40% of the species were singletons, 98% of the species had a total abundance lower than 10 individuals, and approximately half of the species were found only in one sample. The highest species richness was recorded in the slope (500–1,000 m), despite the elevated levels of barium and hydrocarbons at those depths. This area was also characterized by the most unique species composition. Species accumulation curves did not reach an asymptote, suggesting an undersampling of the area and a great rarity of the species. Results of the canonical correspondence analysis (CCA) and cluster analysis demonstrated a positive influence of oxygen concentration and fluorescence, particularly in the shallow shelf sites (25–50 m), which were characterized by a higher abundance of Tanaidacea. Depth zonation of tanaidacean communities with a division between shallow-water taxa (Leptocheliidae Lang, 1973 and Kalliapseudidae Lang, 1956) through families with wide bathymetric range (Pseudotanaidae Sieg, 1976, Apseudidae Leach, 1814) to the true deep-sea forms (Paranarthrurellidae Błażewicz, Jóźwiak and Frutos, 2019) is also evident. We further discuss the problems associated with multivariate analysis of highly speciose but less abundant taxa.